Gendered exclusion in agricultural water governance: A case study in district Okara, Pakistan - Waqar, Kanwal; Hafeez, Mohsin (CAB International, 2025)
Background: Gender disparities in agricultural water management persist globally, yet context-specific evidence from Pakistan remains limited. This study investigates the systemic barriers to gender equity in water governance in District Okara, Punjab, which is a critical agricultural region due to its highly fertile land, extensive canal irrigation system, and significant production of key crops and livestock. Methods: A mixed-methods approach was employed, integrating: (i) a quantitative survey of 402 households (ii) a qualitative gender analysis of national and provincial water policies, and (iii) stakeholder consultations with government departments and Water User Associations (WUAs). Results: The findings reveal a profound disconnect between women’s labor and their decision-making power. Despite contributing 3–4h of daily agricultural labor, only 3% women involved in of on-farm decisions. Policy analysis shows the National Water Policy 2018, and provincial water acts i.e, Punjab Water Act 2019 & KP Water Act 2020 are gender-blind. Institutional barriers are evident, with women in WUAs often serving as “silent observers” and 92% of women requesting flexible training formats to overcome time poverty, exemplified by their 15–30 min daily water collection burden. Conclusion: Gender-blind policies, socio-cultural norms, and institutional constraints collectively sustain women’s exclusion from water governance. Transformative change requires enforceable gender quotas in WUAs, awareness and literacy programs and gender-responsive trainings targeting institutions and WUAs. These interventions are essential for advancing inclusive, SDG-aligned water management in Pakistan and comparable contexts, ensuring equitable access, resilience, and sustainable resource use.